Serra do Navio, Guiana Shield lowland area, Brazil: a region with high diversity of Squamata - Prudente, Ana Lúcia C. (2020)
The Guiana Region is the area bordered by the Orinoco and Negro rivers to the west, by the Amazonas River to the south and by the Atlantic Ocean to the north and east. This area is a biogeographic unit known as the Guiana Shield, with a variety of landscapes. Located in the extreme north of Brazil, in the Guiana Shield lowlands, the state of Amapá presents great diversity of habitats. In this study we provide composition and diversity data of the Squamata from Serra do Navio (SN) region, in the northeastern part of the state of Amapá, Brazil, a lowland area of the Guiana Shield. The species list was based on data obtained from herpetological collections and collection expeditions carried out at 10 sites in the municipalities of Pedra Branca do Amapari and Serra do Navio. We consider literature data from 14 sites and SN data to compare the composition of herpetofauna between the lowland and highland areas in the Brazilian Amazon.We recorded 95 species, including 57 snakes, 36 lizards, and two species of amphisbaenians. Atractus aboiporu, A. trefauti, and Erythrolamprus rochai were described from the data collected in this study. The Squamata community of SN consists mainly of diurnal lizards and nocturnal snakes, with terrestrial and cryptozoic habits, present in pristine and altered environments. The most abundant species of lizard and snake were Loxopholis guianense and Atractus latifrons, respectively. The SN region has 17 exclusive Squamata species, with a fauna similar to the Tumucumaque Mountains and northern Pará sites, geographically closer regions with similar altitudes.